Impact of universal health insurance on total ischemia time and door-to-balloon time in STEMI: A single-center study from a geographical adverse region - Amar Nath Upadhyay; Manira Dhasmana; Barun Kumar (Wolters Kluwer Medknow Publications, 2022)
Introduction: We studied the impact of a Universal Health Insurance (UHI) Scheme introduced in India on total ischemia time (an important determinant of ST-elevation myocardial infarction [STEMI] outcome). Materials and Methods: This is a retrospective hospital-based comparative study which evaluated the total ischemia time (min) of all the patients presenting with STEMI and undergoing primary angioplasty before (Group A) and after (Group B) implementation of this scheme. Results: A total of 221 patients (mean age: 54.18 ± 13.02 years in Group A and 57.59 ± 11.42 years in Group B) were included in the study. Median pain to first medical contact time was 300 and 360 min (P = 0.49), whereas the median first medical contact to percutaneous coronary intervention PCI center time was 330 and 210 min (P = 0.32), for Groups A and B, respectively. A statistically significant difference was noted in the mean door-to-device time between two groups (67.46 ± 33.10 min in Group A vs. 58.48 ± 12.99 min in Group B; P = 0.02). Conclusions: A significant difference in door-to-balloon time was found after implementation of UHI, but total ischemia time was no different. It emphasizes the importance of establishing a system of STEMI care that can decentralize the benefits of early reperfusion like hub-and-spoke model.